Categorizing Online Climate Change Interpretation Across the National Park System. Issue 1 (April 2021) - Roberts, Ryan; Holly, Matt; Perez, Larry
Climate change effects are evident across the National Park System, and units are encouraged to provide proactive, meaningful interpretation on the issue to cultivate informed partners and encourage collaborative stewardship. But climate change is not currently interpreted across all units of the National Park System. Anecdotal observations suggest some units highly prioritize the topic, while others do not. Thus, we conducted an assessment of current online climate change interpretation across the National Park System as one means of quantifying park engagement. Results suggest that—of the 391 units included in the analysis—37% interpreted climate change in some manner online as of February, 2019. Though our method of analysis does not fully describe park interpretive efforts, our findings provide a baseline measure of online interpretation and help to prioritize future training and support. Furthermore, our work provides a minimally intensive approach for future assessment of online climate change interpretation.